Enhancement of sustainable coastal management through financial literacy and capacity building in Ambulu Mangrove ecotourism village - Utami Arie Susetio; Johan Johan; Chamidah Nurul; Angraeni Renita; Reni Cica (BIO Web of Conferences)
Mangrove forests in Ambulu Village, Cirebon Regency, play a vital ecological role and offer significant potential for community-based ecotourism. However, the Caplok Barong tourism community lacked financial literacy, particularly in cost management and pricing, resulting in operational inefficiencies and unsustainable practices. This study aims to strengthen the community’s capacity through structured interventions focused on Cost of Goods Sold (COGS) calculation and sustainable tourism package development. The program employed a three-phase approach: preparatory assessments, training and mentoring, and participatory evaluation. Educational modules introduced fixed and variable cost identification, markup pricing strategies, and the development of ecotourism attractions such as mangrove planting (tailored for different age groups), boat tours, and traditional “bancakan” seafood experiences. Pre- and posttraining assessments demonstrated a 26% average improvement in financial literacy indicators. The community also adopted more disciplined financial recordkeeping and diversified its tourism offerings. Digital promotion through flyers and WhatsApp outreach increased engagement, attracting interest from schools and conservation-focused tourists. This initiative highlights the critical intersection of financial education and sustainable tourism development, positioning COGS literacy as a strategic tool for community empowerment. The integrated model replicates other coastal areas seeking to align ecological conservation with socio-economic resilience.